2017
DOI: 10.1007/s00270-017-1769-z
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetically Navigated In Situ Fenestration of Aortic Stent Grafts: Pilot Animal Study of a Novel Fenestrated EVAR Approach

Abstract: Electromagnetically navigated in situ aortic fenestration for juxtarenal aortic stent grafts was feasible in a healthy animal model. Identified remaining challenges were: shortening the procedure to avoid long warm ischemia times, using an aortic aneurysm animal model, and improving the stability of the stent graft material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 16 publications
0
6
0
1
Order By: Relevance
“…The ability to combine a sensor-equipped steerable catheter with EM navigation guidance has already been successfully tested in vivo by Penzkofer et al, 4 who reported the use of this technique to perform in situ fenestrations on porcine models. Tystad Lund et al 5 suggest a learning curve with EM-guided catheterization of renal arteries, with a significant difference in median duration time between before and after 30 attempts.…”
Section: Discussionmentioning
confidence: 99%
“…The ability to combine a sensor-equipped steerable catheter with EM navigation guidance has already been successfully tested in vivo by Penzkofer et al, 4 who reported the use of this technique to perform in situ fenestrations on porcine models. Tystad Lund et al 5 suggest a learning curve with EM-guided catheterization of renal arteries, with a significant difference in median duration time between before and after 30 attempts.…”
Section: Discussionmentioning
confidence: 99%
“…In a swine model, complex endovascular procedures such as in situ fenestration of endografts has been performed using EM navigation systems. 12 The endovascular specialists in this trial had no prior experience or training with the AR headset or EM tracking systems. The intuitive nature of this technology is associated with a minimal learning curve.…”
Section: Discussionmentioning
confidence: 99%
“…A tri-dimensional fusion technique, sensorised guiding, and electromagnetically navigated devices could be helpful in this setting. 21,22 Regarding fabric strength modification, a significant mechanical strength loss was observed following both MISF and LISF. In fact, the hole creates a zone where there is a lack of fabric material, which corresponds to (i) the material degraded with the fenestration and (ii) the cutting balloon enlargement.…”
Section: Discussionmentioning
confidence: 99%